Disaster Mitigation with Local Wisdom in the Community of West Sumatra - Ramadhan, Aditya; Taqiyuddin (PT. Pubsains Nur Cendekia, 2024)
West Sumatra Province is an area that has often been hit by disasters since ancient times, such as floods, earthquakes and tsunamis. This is related to geographical conditions where tectonic plates often move. Natural disasters have changed the way people live to adapt to face this phenomenon. This research aims to describe the form of local wisdom of the Minang community in mitigating disasters that often hit the area. The method used is a literature study developed descriptively with secondary data from relevant research on the topic. The results found that the local wisdom of the Minang community as a form of mitigation is in the form of proverbs with a philosophy of harmony with nature, the shape of the house and philosophical principles in the order of life so that they are able to live in harmony with nature conservation.